Dog-human dietary relationships in Yup'ik western Alaska: The stable isotope and zooarchaeological evidence from pre-contact Nunalleq. (February 2018) - McManus-Fry, Ellen; Knecht, Rick; Dobney, Keith; Richards, Michael P.; Britton, Kate
Abstract: Historically and ethnographically dogs have been an important resource for Arctic and subarctic societies — providing protection, fur and meat, as well as aiding hunting and transportation. The close relationship between dogs and humans has also been used by archaeologists to draw inferences about human society (particularly in terms of diet and subsistence) from various analyses of their remains. Here, we apply the complementary approaches of stable isotope and zooarchaeological analysis to dog remains from the permafrost-preserved, pre-contact Yup'ik village site of Nunalleq ( c . CE 1300–1750), in coastal western Alaska, specifically to investigate dog-human dietary relationships and the role that dogs played in this community. Zooarchaeological data indicate an abundance of dogs at the site, with butchery marks suggesting that they were processed for meat. Stable isotope analysis of multiple tissues indicates dog diet was largely based on fish (particularly salmonids), with possible short-term increases in marine mammal consumption. Comparison with data from contemporaneous human hair from Nunalleq indicates a close similarity between human and dog diets, supporting the use of dogs as a proxy for human palaeodiet in societies at high-latitude societies consuming significant amounts of animal protein. Highlights: δ 13 C and δ 15 N data indicate dog diet at Nunalleq was dominated by salmonids. Domestic dog diet similar to human diet at Nunalleq (Britton et al., this volume ) Analyses of fur and claw samples suggest seasonal and inter-individual variability. Zooarchaeological evidence indicates butchery and human consumption of dogs.